Plotinus on Transmigration: a Reconsideration - Stamatellos, Giannis (Journal of Ancient Philosophy, 2013)
The aim of this paper is to reconsider Plotinus’ account of transmigration in the light of his dual-aspect theory of the soul. It is argued that transmigration is discussed in the Enneads only in relation to the lower perceptible part of the soul. The higher intelligible part of the soul remains undescended and uninvolved in any kind of transmigration. Plotinus’ treatment of transmigration also aims at emphasizing the soul’s higher life of virtue. The noble soul concentrates on its higher intelligible part in constant contemplation of the Forms without being affected by its lower perceptible part and therefore transmigration.